Comparison of Learning Cooperative Type NHT (Numbered Heads Together) with Conventional Learning Against The Results of The Study in The Review of The Interest Students of Class X - Ineza Ghaisani Mayzura; Agus Efendi; A G A.G Tamrin (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2018)
This research aims to know (1) what is the difference between the influence of the application of the learning model NHT (Numbered Heads Together) with the conventional model against the results of student learning; (2) whether there is influence of interest in student learning outcomes; (3) whether there is a iteraksi between the model of learning with student learning interest against the results of student learning. The selected sample was 72 students of class X 2017/2018 school year. This research uses descriptive types of quantitative research. Data collection is done by the spread of the question form and documentation. Data analysis variansi Analysis using two directions with the same cells. The research results obtained explains that (1) the learning approach with NHT and conventional produce learning material on the same virtual classroom (2) learning Interest of students who follow learning learning model with more NHT high compared to the interest of students who follow the conventional learning content virtual classroom discussion (3) there is no significant interaction between the approach of learning and learning interest of students towards the learning results in the subject class Maya. The students, who follow learning approach to learning that results had NHT equals celebrates student learning model with conventional lessons. High interest has more students for lessons on the virtual classroom learning model with NHT.